Saer versus Aira: versões de uma antropologia especulativa - Antonio Marcos Pereira (Estudos de Literatura Brasileira Contemporânea)
The paper proposes a confrontation of the work of two authors, Juan José Saer and César Aira, markedly different in the structures of reception their works bring forth, and that we might translate particularly in the way their relationship with “the contemporary” is perceived, resulting in specific placings in certain genealogies and in the production of their respective inscriptions in recent literary history in Latin America. The examination of fictional objects such as Saer’s La pesquisa and Aira’s Parmenides leads one to find ambivalent solicitations of the allegedly historical fact and its relation to fiction that are hereby presented as oportunities to operate critically towards the structures of established reception and criticism of the work of both authors.